Biologic therapies committee. What does it provide? - Virginia Martínez-Santana; Sonia Fernández-Cañabate; Eva Fernández-Cañabate; Antoni Boix-Montañés; Núria Miserachs-Aranda; Pilar Modamio-Charles (Elsevier, 2021)
Objective: To assess the general healthcare impact of a Biological Therapies Commitee (immune-mediated inflammatory diseases) through prescription habits, pre-biological studies and immunization. Method: A quasi-experimental study was conducted on all naïve patients of legal age who started treatment with a biological agent for an immune- mediated inflammatory disease the year before and the year after the creation of the Biological Therapies Committee. Results: A total of 31 patients treated in 2016 and 40 patients treated in 2018 were included. Prescriptions of tumor necrosis factor alpha inhibitor drugs decreased in 2018 (from 80.6% to 45.0%, p < 0.05), while prescriptions of interleukin 12/23 inhibitors increased (from 12.9% to 35.0%, p < 0.05). Tuberculosis screening was statistically different between the two periods: the number of interferon gamma release assays performed was higher in 2018 (from 9.7% to 80.0%, p < 0.01) and the proportion of patients who successfully underwent chemoprophylaxis was higher in 2018 (from 36.4% to 81.8%, p < 0.05). The proportion of tests requested for the study of viral pathologies and the number of vaccines administered were also higher in 2018. Conclusions: The development of a specific Biological Therapies Committee allows healthcare improvements, contributing to a deeper understanding of the medications and to preventing the infection- related adverse events. It would therefore seem advisable to develop specialized committees akin to the Biological Therapies Committee in other domains.